A leader in need is a leader indeed? The influence of leaders' stress mindset on their perception of employee well‐being and their intended leadership behavior. Issue 4 (14th November 2021) - Kaluza, Antonia J.; Junker, Nina M.; Schuh, Sebastian C.; Raesch, Pauline; von Rooy, Nathalie K.; van Dick, Rolf
Abstract: The ability to respond appropriately to employees' work‐related well‐being requires leaders to pay attention to their employees' well‐being in the first place. We propose that leaders' stress mindset, that is, the belief that stress is enhancing versus debilitating, may bias their perception of employees' well‐being. We further propose that this judgment then influences leaders' intention to engage in or refrain from health‐oriented leadership behavior, to express higher performance expectations, or to promote their employees. We expect this process to be stronger if leaders strongly identify with their team, increasing their perceived similarity with their employees. In three experiments ( N 1 = 198, N 2 = 292, N 3 = 250), we tested the effect of participants' stress mindset on their intention to show certain leadership behaviors, mediated by their perception of employee well‐being (emotional exhaustion, somatic symptoms, work engagement) and moderated by their team identification. Our findings largely support the association between stress mindset and the perception of well‐being. The results for the proposed mediation and the moderating function of identification were mixed. Overall, the results emphasize the critical role of leaders' stress mindset and may, thus, improve health promotion in organizations by helping leaders to adequately recognize employees' well‐being and respond appropriately.